Improvement Quality of Financial Statements Through Application of Goverment Accounting Standards and Good Governance - Nurmiati, Nurmiati; Lubis, Bastian (Patria Artha Journal of Accounting dan Financial Reporting, 2018)
The Study aims to analyze improvement quality of financial report through application of governance accounting standards and good governance. Analyzed the data obtained by usinganalysis quantitative. Quantitative analysis includes multiple regression analysis, coefficient ofdetermination analysis and hypothesis throuhh t test and f test. The results of research andstatistical analysis using shows that the quality of financial statements is influenced by theapplication of government accounting standards and good governance.